2018
DOI: 10.3390/healthcare6010025
|View full text |Cite
|
Sign up to set email alerts
|

A 40-Day Journey to Better Health: Utilizing the DanielFast to Improve Health Outcomes in Urban Church-Based Settings

Abstract: Background: As the costs associated with obesity increase, it is vital to evaluate the effectiveness of chronic disease prevention among underserved groups, particularly in urban settings. This research study evaluated Philadelphia area Keystone First members and church participants enrolled in a group health education program to determine the impact of the Daniel Fast on physical health and the adoption of healthy behaviors. Methods: Participants attended six-weekly health education sessions in two participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The use of SMS text messages in the LEAN study did not appear to result in greater weight loss compared with most other church-based studies targeting African American adults [ 38 ]. However, our satisfaction data showed that SMS text messages were well-received, similar to recent studies [ 25 , 26 , 37 ]. Of note, the majority of LEAN participants responded to SMS text messages even though they were not required to do so, and higher text message response was associated with higher percent body fat loss.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The use of SMS text messages in the LEAN study did not appear to result in greater weight loss compared with most other church-based studies targeting African American adults [ 38 ]. However, our satisfaction data showed that SMS text messages were well-received, similar to recent studies [ 25 , 26 , 37 ]. Of note, the majority of LEAN participants responded to SMS text messages even though they were not required to do so, and higher text message response was associated with higher percent body fat loss.…”
Section: Discussionsupporting
confidence: 91%
“…The unique component of the LEAN study was the use of SMS text messages in a randomized controlled trial targeting African American adults. Three recent studies of African American adults have utilized SMS text messages to assist in the initiation of behavioral change in a church-based setting [ 25 , 26 , 37 ]; the SMS text messaging system in these studies included personalization, support, and delivering recipes and meal plans. They also showed within-group changes in weight loss or physical activity outcomes across 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Systematic reviews have found mobile messaging to be a promising approach for promoting healthy eating and physical activity. 17,18 The majority of studies that employed mobile messaging in church settings, including three studies with AA populations, [19][20][21] found that the approach was promising but required further research. One study reported that respondents did not want to participate in healthy living activities beyond the messages, 20 while the other suggested that messaging be used as part of a more comprehensive response to promoting healthy weight.…”
Section: Introductionmentioning
confidence: 99%
“…19 Another study successfully combined messaging with a structured diet and cooking classes implemented during the 40 days before Easter. 21 Thus, combining mobile messaging with other church-based activities may increase participants' exposure to healthy living content, but it is unclear how acceptable this approach would be to congregants. Another study described the successful integration of a mobile messaging component into a multi-level, church-based program; however, the study focused on prostate cancer prevention.…”
Section: Introductionmentioning
confidence: 99%